Peningkatan Hasil Belajar PAI Dengan Menggunakan Metode Card Sort di SD Negeri 09 Pasar Ladang Panjang - Irliyanti, Delma (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to improve student learning outcomes in Islamic Religious Education (PAI) at SD Negeri 09 Pasar Ladang Panjang through the application of the Card Sort method. This method is expected to address the existing issues, such as low student learning outcomes that are still below the Criteria of Minimum Mastery (KKTP). The study focuses on fourth-grade students on the topic of Aqeedah about Belief in the Messengers of Allah. Based on observations, many students are less active in learning due to the dominance of the boring lecture method. Therefore, the Card Sort method, which is fun and involves collaboration among students, is expected to enhance student engagement and creativity in learning. This study uses a Classroom Action Research (CAR) approach, with two main research questions: how is the implementation of the Card Sort method in PAI learning and does this method improve student learning outcomes? The expected outcome is an improvement in student learning outcomes, reflected in test scores and increased active participation during the lessons.